Gastritis and gastric campylobacter-like organisms in patients without peptic ulcer. Issue 741 (July 1987) - Sethi, P.; Banerjee, A. K.; Jones, D. M.; Eldridge, J.; Hollanders, D.
Abstract : Gastric biopsy specimens were obtained from 83 patients without peptic ulcer disease and analysed histologically. Culture and serological studies were done on the last 64 patients. The patients were divided into two age groups (young and old groups.) In 34 patients with chronic superficial gastritis, gastric campylobacter-like organisms (GLCO) were identified histologically in 91% and grown on culture in 88%: antibody to GCLO was detected in 81%. No age-related difference in the prevalence of the organism was demonstrated. In the 23 patients with atrophic gastritis (all elderly), presence of the organisms appeared to be related to the presence of an inflammatory cell infiltrate into the gastric mucosa. These figures for the prevalence of the organism in this selected group of patients are similar to those reported in previous studies of unselected patients which included those with peptic ulcer. This suggests that GCLO is unlikely to be causally related to peptic ulcer.